(untitled) (Research, Society and Development, 2020)
Mushroom consumption in Brazil has strongly increased with the oriental restaurants expansion and although has not yet been part of the population diet, consumer interest in mushrooms is growing. The main mushrooms produced in Brazil are Paris mushrooms (Agaricus bisporus or bitorquis), shiitake (Lentinula edodes), shimeji (Pleurotus ostreatus) and hiratake (Pleurotus sajor caju). Brazilian mushroom production is not able to attend the demand, and it is necessary to import the product from other countries to supply the domestic market, indicating that there is room for increase the production. Besides, mushrooms cultivation can be carried out in small areas, being an important income alternative for small producers. The mushrooms production is already a reality in Londrina - PR region, that goes primarily to the local and regional market. However, there is no characterization of this activity in this region. The objective of this study is to raise local experiences of mushroom production and point out main challenges and potential opportunities for production in the region. For this, a questionnaire was applied to some producers, gathering information such as the main species of mushrooms produced, the production system adopted, the marketing destination, among others. The results indicated that fungiculture in the region is recent and still poorly organized. The main obstacles pointed out by producers are the lack of technical assistance, the need to import inputs from other states and competition with São Paulo’s mushroom prices.